2011
DOI: 10.1002/art.30543
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 and transforming growth factor β1 induce precocious maturation of articular cartilage

Abstract: Objective. We have discovered that a combination of fibroblast growth factor 2 and transforming growth factor ␤1 induce profound morphologic changes in immature articular cartilage. The purpose of this study was to test the hypothesis that these changes represent accelerated postnatal maturation.Methods. Histochemical and biochemical assays were used to confirm the nature of the morphologic changes that accompany growth factor stimulation of immature bovine articular cartilage explants in serumfree culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 48 publications
2
28
0
2
Order By: Relevance
“…Many efforts have been made to study the molecular signals involved in FGF-2 induced proliferation of chondrocytes [43][44][45], with the hope of preventing the formation of fibrous cartilage tissue caused by FGF-2 treatment [ 46,47]. Our data uncover a positive role of FGF-1 in proliferation of hPCs, at least in co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 65%
“…Many efforts have been made to study the molecular signals involved in FGF-2 induced proliferation of chondrocytes [43][44][45], with the hope of preventing the formation of fibrous cartilage tissue caused by FGF-2 treatment [ 46,47]. Our data uncover a positive role of FGF-1 in proliferation of hPCs, at least in co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 65%
“…*P < 0.05, n 04 stiff tissue is formed, which has an even distribution of PGs (Miyazaki et al 2010). A recent investigation has also shown that the combined presence of FGF-2 and TGF-β 1 accelerates maturation-type changes in tissue stiffness, collagen fibril architecture, and cross-linking, and even more importantly, the zonal fine structure is obtained only in the presence of growth factors (Khan et al 2011). Growth factors also cause a 52% reduction in the height of the explants (Khan et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…It has been recently shown that molecular signalling alone can induce and enhance AC maturation in vitro. A combination of growth factors (FGF-2 and TGFβ1) induce collagen remodelling and significantly enhance (229 % increase) mechanical stiffness and change in the microanatomic structure of cartilage explants from immature calves in vitro without any loading of the construct (Khan et al, 2011). Enhanced crosslinking of the collagen fibrils is also observed.…”
Section: Wwwecmjournalorg C Cluzel Et Al Articular Cartilage Develmentioning
confidence: 97%